Changes in Cervical Sagittal Alignment after Single-Level Posterior Percutaneous Endoscopic Cervical Diskectomy. (February 2015) - Kim, Chi Heon; Shin, Kyung-Hyun; Chung, Chun Kee; Park, Sung Bae; Kim, Jung Hee
Study Design: Case series. Objective: Posterior percutaneous endoscopic cervical diskectomy (PECD) can preserve the disk in patients with a foraminal disk herniation. However, progressive angulation at the operated segment is a concern, especially for patients with cervical lordosis < 10 degrees. The change in cervical lordosis after posterior PECD was analyzed. Methods: Medical records were reviewed of 32 consecutive patients (22 men, 10 women; mean age, 49 ± 12 years) who had single-level foraminal soft disk herniation. The operation levels were as follows: C4–5 in 1 patient, C5–6 in 12, C6–7 in 18, and C7–T1 in 1. All patients were discharged the day after the operation, and neck motion was encouraged. All patients were followed for 30 ± 7 months (range, 24 to 46 months), and 21/32 patients (66%) had radiographs taken at 25 ± 11 months (range, 12 to 45 months). Radiologic parameters were assessed, including cervical curvature (C2–7), segmental Cobb's angle (SA), and anterior and posterior disk height (AH and PH, respectively) at the operative level. Results: At the last follow-up, 29/32 patients (91%) had no or minimal pain, and 3/32 patients had occasional pain. SA, AH, and PH were not significantly changed. Cervical lordosis < 10 degrees was present in 10/21 patients preoperatively and in 3/21 patients at the last follow-up. For patients with cervical lordosis < 10 degrees, cervical curvature changed from −2.5 ± 8.0 to −11.3 ± 9.3 degrees ( p = 0.01). For patients with cervical lordosis ≥ 10 degrees, cervical curvature changed from −17.5 ± 5.8 to −19.9 ± 5.7 degrees ( p = 0.24). Conclusions: Cervical curvature does not worsen after posterior PECD.